Facile fabrication of hierarchical carbon fiber–MoS2 ultrathin nanosheets and its tribological properties. Issue 65 (23rd June 2016) - Chen, Beibei; Li, Xiaofang; Li, Xiang; Yang, Jin; Peng, Weixiang; Dong, Jinze; Li, Changsheng; Song, Haojie
Abstract : A novel lubricating material of hierarchical carbon fiber–MoS2 ultrathin nanosheets (CF–MoS2 ) was fabricated by one-step hydrothermal solution reaction method. Abstract : A novel lubricating material of hierarchical carbon fiber–MoS2 ultrathin nanosheets (CF–MoS2 ) was fabricated by one-step hydrothermal solution reaction method. The corresponding phase composition, morphology and formation mechanism were systematically determined by XRD, FESEM and TEM. And the effects of CF–MoS2 on the tribological properties of epoxy (EP) were investigated comparatively using universal micro-tribotester-2 (UMT-2). Results showed that MoS2 ultrathin nanosheets with the thickness of 5–8 nm and size of 300–500 nm were synthesized successfully. And several MoS2 nanosheets assembled together in flower-like shape and were attached onto CF surface uniformly. Furthermore, the XRD pattern analysis of as-prepared CF–MoS2 confirmed that MoS2 was in the form of hexagonal phase. Besides, the shore hardness of EP matrix was improved obviously by the incorporation of CF–MoS2, suggesting the load-carrying capacity of EP was enhanced. More importantly, EP/CF–MoS2 composite had much better tribological properties than EP and other EP-based composites (EP/CF and EP/MoS2 ) because of the reinforcement effect of CF and lubricating effect of MoS2 . In particular, EP/CF–MoS2 composite still possessed good friction-reducing and anti-wear properties under heavy loads. Namely, hierarchical CF–MoS2 was a promising additive to be used in tribology field.